Voice of the voiceless: examining Bandungbergerak as local alternative media in Bandung - Aliifa, Dzikrifa; Damayani, Ninis Agustini; Rizal, Edwin; Maryani, Eni (Faculty of Communications Science, Dr. Soetomo University, 2026)
The dominance of mainstream media often sidelines the voices of marginalised groups, prompting the emergence of alternative media as a form of symbolic resistance. Bandungbergerak, a local alternative media outlet, consistently highlights progressive issues and amplifies the interests of vulnerable communities in Bandung. This study examined how Bandungbergerak represents minority groups in Bandung, how it curates and publishes related issues, and how it navigates the challenges of sustaining an alternative discursive space. The research employed a qualitative approach through in-depth interviews. The findings reveal that Bandungbergerak consistently provides a platform for marginalised voices, adopting humanistic and participatory journalistic practices. Issue selection is based on public urgency and is carried out in collaboration with local communities. Despite its contributions, the media faces structural challenges, including limited resources, social backlash and digital threats. This study emphasised that supporting a diversity of voices in alternative local media is not just about promoting inclusivity, but also about democratising media ecosystems at the local level.